POTRET KEKERASAN TERHADAP LANSIA PEREMPUAN DI INDONESIA - Darma Kelana Putra (Prodi Sosiologi FISIP Universitas Teuku Umar, 2019)
Violence against elderly women is one of the long-standing cultural problems in society, and this issue has only become the world's attention when WHO announced a program to eliminate violence against the elderly that was welcomed by the Government of Indonesia by issuing “Peraturan Menteri Pemberdayaan Perempuan dan Perlindungan Anak Nomor 24 Tahun 2010 tentang Model Perlindungan Perempuan Lansia yang Responsif Gender” as a positive response to tackling the issue. The main question in this study is how the portrait of violence against elderly women in Indonesia and why this issue is difficult to reveal. The study was conducted with descriptive qualitative methods that aimed to describe the exact characteristics of an individual, circumstances, symptoms or certain groups in society, where all data were obtained from literature searches and literature studies. This study concludes that violence against the elderly in Indonesia is a form of gendered ageism that is almost invisible. This practice is more often experienced by elderly women because of intertwined identity factors, especially when they come from the lower classes, do not have income, and experience physical and mental disability. Violence against elderly women in Indonesia is difficult to reveal because it is in the domestic sector (family matter), besides that elderly women who are victims of violence also have various obstacles in conveying their problems so that they are more likely to choose to remain silent.